The Role of Family Culture on the Transgenerational Transfer in Colombian Family Business - Willian Klinger Mosquera; María Piedad López Vergara; Diógenes Lagos Cortés (Journal of Evolutionary Studies in Business, 2024)
This exploratory research seeks to identify the role of family culture in the transgenerational transfer in Colombian family businesses. The sample was selected for convenience from a list of companies provided by the Chocó Chamber of Commerce (Colombia). To be included in the sample, the companies had to meet the following criteria: (a) Be over 25 years; (b) be in operation; (c) have a turnover of more than 265,000 dollars (1,000 million Colombian pesos) in the previous year; and (d) have an intention of succession to the next generation. A semi-structured interview was applied to members of five family businesses in the department of Chocó. It was evidenced that the type of family culture influences the transgenerational transfer process through the preparation for succession, values, decision-making process, and level of commitment.